Physical Environment And Sustainable Development - Aminah Harahap; Yenni Khairani Lubis (Institut Agama Islam Negeri Padangsidimpuan, 2025)
Physical environment plays a strategic role in supporting sustainable development. Increasingenvironmental damage, such as climate change, pollution, and exploitation of natural resources, shows that development that does not consider environmental aspects will have a serious impact on human life. Therefore, Physical environment is an important instrument for shaping public awareness, knowledge, attitudes, and behavior to be more responsible towards the environment. This study aims to examine the concept of Physical environment and its relationship with sustainable development through a literature review approach. Data were obtained from various sources, including books, national and international scientific journals, and official documents from relevant institutions. The results of the study show that Physical environment plays a role in instilling values of sustainability, increasing environmental literacy, and encouraging community participation in maintaining a balance between social, economic, and environmental factors. Therefore, a key step towards achieving sustainable development is to integrate Physical environmentinto formal and informal physics institutions.